PENGARUH KOMPENSASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU - Rosanti, Berliana Adhefita Alsafira; Sudiro, Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of depression and organizational commitment on teacher performance at Madrasah Aliyah Negeri 2 Malang City. This research uses descriptive research with a quantitative approach. Sampling in this study used a saturated sample technique, namely 79 teacher respondents at Madrasah Aliyah Negeri 2 Malang City, the data collection method used was a questionnaire, while the data analysis used in this study was carried out by testing validity, reliability testing, testing the coefficient of determination, classic assumption test, and hypothesis testing which consists of F test and t test using SPSS 24. The results showed that the influencer was positive and significant on teacher performance. This means that the existence of triggers causes an increase in teacher performance in Madrasah Aliyah Negeri 2 Malang City. Second, Organizational Commitment has a direct positive effect on teacher performance. This means that with an increase in organizational commitment to each teacher, it results in an increase in teacher performance at Madrasah Aliyah Negeri 2 Malang City. Based on the results of this study, it can be interpreted that there is a positive and significant influence of compensation and organizational commitment on teacher performance in Madrasah Aliyah Negeri 2 Malang City.